EX527, a sirtuins 1 inhibitor, sensitizes T-cell leukemia to death receptor-mediated apoptosis by downregulating cellular FLICE inhibitory protein - Rongqi Guo; Yihui Wei; Yating Du; Luyue Liu; Haoqi Zhang; Ruiying Ren; Ruili Sun; Tingting Zhang; Xiwen Xiong; Lijun Zhao; Hongfei Wang; Xiaofang Guo; et al. (Cancer Biology & Therapy)
Death receptor-mediated extrinsic apoptosis system had been developed as a promising therapeutic strategy in clinical oncology, such as TRAIL therapy. However, multiple studies have demonstrated that TRAIL resistance is the biggest problem for disappointing clinical trials despite preclinical success. Targeting cellular FLICE inhibitory protein (cFLIP) is one strategy of combinatorial therapies to overcome resistance to DR-mediated apoptosis due to its negative regulator of extrinsic apoptosis. E × 527 (Selisistat) is a specific inhibitor of SIRT1 activity with safe and well tolerance in clinical trials. Here, we show that E × 527 could strengthen significantly activation of rhFasL-mediated apoptotic signaling pathway and increased apoptotic rate of T leukemia cells with high expression of cFLIP. Mechanically, Inhibition of SIRT1 by E × 527 increased polyubiquitination level of cFLIP via increasing acetylation of Ku70, which could promote proteosomal degradation of cFLIP protein. It implied that combinatorial therapies of E × 527 plus TRAIL may have a potential as a novel clinical application for TRAIL-resistant hematologic malignancies.